PEMODERASIAN FENG SHUI TERHADAP HUBUNGAN ANTARA PLACE DAN BUSINESS LONGEVITY - Sugiharto Putra, Calvin; Alessandro Effendy, Junko (Jurnal Keuangan dan Bisnis, 2023)
This study aims to determine the effect of place variable on business longevity, and the moderating role of feng shui on the relationship between place and business longevity. This research was conducted quantitatively using the moderation effect test. The analytical tool in this study uses the SMARTPLS-3 application. The total population in this study was 55 Chinese business owners who are members of the C community in Surabaya. After the researchers distributed the questionnaires, the questionnaires that could be used were 41 respondents. Statistical tests used in this study include convergent validity test, discriminant validity test, reliability test, hypothesis test and determination coefficient test. The results of the study show that the place variable has an effect on business longevity, and the feng shui variable negatively moderates the relationship between place and business longevity.